The maize OST1 kinase homolog phosphorylates and regulates the maize SNAC1-type transcription factor. - Belmiro Vilela; Alicia Moreno-Cortés; Agnese Rabissi; Jeffrey Leung; Montserrat Pagès; Victoria Lumbreras (PLoS ONE, 2013)
The Arabidopsis kinase OPEN STOMATA 1 (OST1) plays a key role in regulating drought stress signalling, particularly stomatal closure. We have identified and investigated the functions of the OST1 ortholog in Z. mays (ZmOST1). Ectopic expression of ZmOST1 in the Arabidopsis ost1 mutant restores the stomatal closure phenotype in response to drought. Furthermore, we have identified the transcription factor, ZmSNAC1, which is directly phosphorylated by ZmOST1 with implications on its localization and protein stability. Interestingly, ZmSNAC1 binds to the ABA-box of ZmOST1, which is conserved in SnRK2s activated by ABA and is part of the contact site for the negative-regulating clade A PP2C phosphatases. Taken together, our results indicate that ZmSNAC1 is a substrate of ZmOST1 and delineate a novel osmotic stress transcriptional pathway in maize.